2003
DOI: 10.1063/1.1596385
|View full text |Cite
|
Sign up to set email alerts
|

Study on interfacial dislocations of Si substrate/epitaxial layer by self-interstitial decoration technique

Abstract: Trapping of migrating Si interstitials at substrate/epitaxial interfaces during high-energy Si ion bombardment has been observed. It shows that the interface of Si/Si layer, grown by molecular-beam epitaxy, is a strong sink for self-interstitials during MeV bombardment at room temperature. We reported the finding and applied it as a decoration technique to study evolution of interfacial dislocations. After the thermal annealing of Si/Si layers at a temperature ranging from 450 to 600 °C, samples were bombarded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(17 reference statements)
1
0
0
Order By: Relevance
“…Previous study has shown the trapping of migrating Si interstitials at Si/ Si interfaces during high-energy self-ion bombardment. 6 The present study shows that the Si/ Si interface can be a strong trapping site for H atoms as well.…”
supporting
confidence: 52%
“…Previous study has shown the trapping of migrating Si interstitials at Si/ Si interfaces during high-energy self-ion bombardment. 6 The present study shows that the Si/ Si interface can be a strong trapping site for H atoms as well.…”
supporting
confidence: 52%